Scarred from the past or afraid of the future? Unemployment and job satisfaction across European labour markets - Lange, Thomas (Routledge, 2013)
Previous research has shown that both past unemployment and anticipated future unemployment have a detrimental impact on employees' attitudes and behaviours, which may affect organisational performance. Surprisingly, however, very little is known about the relative impact of past unemployment compared with current job insecurity. Although it is possible that both effects operate simultaneously, this paper – focused on employees' job satisfaction and utilising a set of cross-sectional data derived from the European Social Survey 2006–2007 – reports on a strongly pronounced insecurity effect: anticipated unemployment substantially reduces employees' job satisfaction. Interestingly, inclusion of the perceived risk of future unemployment as a separate predictor variable in ordered probit regressions relegates the experience of past unemployment to a statistically insignificant coefficient and thus weakens the ‘scarring’ hypothesis. These results hold true even when several socio-demographic characteristics and proxies for individual personality traits are controlled. Implications for organisations and human resource practitioners and scope for future research endeavours conclude the analysis of the paper.